Lead markets for clean coal technologies: A case study for China, Germany, Japan and the USA - Jens Horbach; Qian Chen; Klaus Rennings; Stefan Vögele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Despite the high CO2 emission intensity of fossil and especially coal fired energy production, these energy carriers will play an important role during the coming decades. The case study identifies the main technological trajectories concerning more efficient fossil fuel combustion and explores the potentials for lead markets for these technologies in China, Germany, Japan and the USA taking into account the different regulation schemes in these countries. We concentrate on technologies that have already left the demonstration phase. This is the case for supercritical (SC) and ultra-supercritical (USC) pulverized coal technologies that are already established. The analysis shows that the typical pattern of a stable lead market only applies to a limited extent. In the 1960s and 1970s, the USA has established a lead market for SC und USC technologies. In the meanwhile, Japan has surpassed the United States, although it started as a typical lag market. Japan has caught up in terms of supply factors, China in terms of price, demand and regulation advantage. This supports the hypothesis that - apart from the demand-oriented lead market model - push factors such as R&D activity play a strong role as well. The advantage of Japan mainly stems from its intensive R&D activities. It can also be observed that some other advantages - such as price and demand advantage - are shifting to China. China is practicing a leapfrogging strategy, and has already become a leader in the market segment of low and middle quality boilers, whereas Japan and Germany still dominate the world turbine market. The conclusion is that lead markets may switch over time to markets with high growth rates, although first mover advantages exist for some market segments such as turbines. First movers have a strong technological expertise which is important in the catching up process of late followers, and they may even profit from the growth in lag countries by exporting and cooperation activities. Thus international technology cooperation is a beneficial process for all involved parties.
urn:nbn:de:bsz:180-madoc-325681
Keywords: 330; Lead Markets; Coal Power plants; Energy Technology; Energy Policy